2017
DOI: 10.6018/red/53/1
|View full text |Cite
|
Sign up to set email alerts
|

Governance decentralisation in education: Finnish innovation in education

Abstract: This paper introduces a Finnish education innovation known as decentralisation in education. The innovation is described based on education policy documents, research papers and two short interviews with national and municipality experts in curriculum design. In a decentralised education system local providers of education (municipalities) and teachers play important roles in the preparation of local curriculum and learning environments, including the use of digital learning tools and environments. Education p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Even though the Core Curriculum offers guidelines for the preparation of local curriculum to a certain extent, local education providers have extensive autonomy, and the preparation process of the local curriculum can take various forms, depending on the context. For example, the stakeholders taking part in the preparation process can vary, and in addition to educational professionals, parents and local non-profit organisations can also take part (Lavonen, 2017). To paraphrase Mølstad (2015), the Core Curriculum forms a strong foundation on which municipalities and schools can develop their work, affording them the flexibility to decide on important common ground that various local curricula can be built on.…”
Section: Finnish Curricular Framework and Curricular Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the Core Curriculum offers guidelines for the preparation of local curriculum to a certain extent, local education providers have extensive autonomy, and the preparation process of the local curriculum can take various forms, depending on the context. For example, the stakeholders taking part in the preparation process can vary, and in addition to educational professionals, parents and local non-profit organisations can also take part (Lavonen, 2017). To paraphrase Mølstad (2015), the Core Curriculum forms a strong foundation on which municipalities and schools can develop their work, affording them the flexibility to decide on important common ground that various local curricula can be built on.…”
Section: Finnish Curricular Framework and Curricular Contextualizationmentioning
confidence: 99%
“…More precisely, in this paper, we study how the concept of multiliteracy, a transversal competence, is contextualized in Finnish local curricula. High degree of autonomy of educational providers in the local level (Lavonen, 2017) and multiliteracy as a new concept in the Finnish educational context, with only little research done so far (Kupiainen, 2016), provide an interesting basis for an examination of how novel competency-based additions to the Core Curriculum are contextualized at local level. In the Finnish educational framework, each municipality is required to refine the Core Curriculum to meet the specific needs and affordances of the particular context (NBoE, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although technology has opened doors to many learning opportunities, the mere application of technology itself is not found to be fruitful. A recent study showed that teachers, especially in Finland, do not see the value and benefits of using digital tools (Lavonen, 2017 ). This shows that the use of digital tools alone may not reap positive outcomes.…”
Section: Communication Language Learning and Technologymentioning
confidence: 99%
“…This shows that the use of digital tools alone may not reap positive outcomes. There is a need to understand the good practices that should come hand in hand with the integration of technical tools in lessons (Lavonen, 2017 ). Moreover, language learning is dependent on human factors or individual differences (see Chap.…”
Section: Communication Language Learning and Technologymentioning
confidence: 99%
“…To understand the contextualisation of multiliteracy from a broader perspective, we focus on the local curricula across Finland. The local curricula provide favourable opportunity to understand contextualisation since Finnish teachers and local education providers have high levels of autonomy and the local curriculum is not just a tool to implement the national core curriculum but is also a pedagogical tool for the development of education (Lavonen, 2017;Mølstad, 2015). The following research questions have guided the research process:…”
Section: Introductionmentioning
confidence: 99%